Interlocking orthogrid: An efficient way to construct lightweight lattice-core sandwich composite structure. (15th September 2017) - Jiang, Shu; Sun, Fangfang; Zhang, Xirui; Fan, Hualin
Abstract: To construct weight efficient aerospace sandwich structures, interlocked orthogrid sandwich composite panels reinforced by carbon fibers were designed, made and tested. The orthogrid is weight efficient in flatwise compression for its strength is greater than usual three-dimensional (3D) lattice truss composite structures. Progressive crushing of the ribs endows the orthogrid long deformation plateau and great mean crushing force (MCF) while most of 3D lattice truss composite structures are usually brittle. Crushing models of lattice truss materials were developed to predict the MCF and it is found that the orthogrid composite has comparable or even better specific energy absorption (SEA) compared with 3D metallic lattice trusses. Forming continuous resin adhesive layers between the facesheets and the orthogrid, the orthogrid sandwich panel has stronger shear strength and is more weight efficient than usual 3D lattice truss sandwich panels jointed by adhesive joints in shear resistance. Through the research, it is concluded that interlocking orthogrid provides a simple but efficient way to construct lightweight sandwich composite.